2016
DOI: 10.1016/j.adro.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of chronic radiation-induced cystitis in mice

Abstract: PurposeRadiation cystitis (RC), a severe inflammatory bladder condition, develops as a side effect of pelvic radiation therapy in cancer patients. There are currently no effective therapies to treat RC, in part from the lack of preclinical model systems. In this study, we developed a mouse model for RC and used a Small Animal Radiation Research Platform to simulate the targeted delivery of radiation as used with human patients.Methods and materialsTo induce RC, C3H mice received a single radiation dose of 20 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…A statistically significant lower bodyweight is observed in irradiated C3H mice in comparison to littermate controls starting at 20 weeks post-radiation ( Figure S1a). This has not previously been observed by us or other groups in C3H mice after irradiation (Zwaans et al, 2016). By 12 weeks post-radiation, graying of the fur, or minor hair loss appears at the site of entry and exit beam in C57BL/6 and C3H mice, respectively, and remains visible until the end of the study ( Figure S1b).…”
Section: Bladder Radiation Causes a Persistent Increase In Micturitsupporting
confidence: 60%
See 4 more Smart Citations
“…A statistically significant lower bodyweight is observed in irradiated C3H mice in comparison to littermate controls starting at 20 weeks post-radiation ( Figure S1a). This has not previously been observed by us or other groups in C3H mice after irradiation (Zwaans et al, 2016). By 12 weeks post-radiation, graying of the fur, or minor hair loss appears at the site of entry and exit beam in C57BL/6 and C3H mice, respectively, and remains visible until the end of the study ( Figure S1b).…”
Section: Bladder Radiation Causes a Persistent Increase In Micturitsupporting
confidence: 60%
“…In this study, we show that radiation increases micturition frequency and decreases primary and average individual void size in C57BL/6 and, in a lesser extent, in BALB/c mice. While our methodology was not suitable to measure micturition patterns in C3H mice, previous studies have demonstrated altered micturition frequency in C3H mice after radiation (Lundbeck, Nielsen, & Stewart, ; Lundbeck, Oussoren, & Stewart, ; Zwaans et al, ). These changes are consistent with a functional decrease in bladder capacity.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations